The effect of ethanol on cortisol metabolism in man : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University. - Evans, Pandora Carlyon (Massey University, 1979)
Methods were developed for the estimation of human plasma cortisol by radioimmunoassay and urinary 6β-hydroxycortisol (6βOHF) by colorimetry after separation by thin layer chromatography (TLC). In addition profiles of urinary neutral steroids were obtained by gas chromatographic separation of methoxime-trimethylsilyl derivatives from urine extracts on a glass capillary column. This approach was found to be more sensitive and reproducible than profile studies based on TLC separation and colorimetric estimation. Pilot studies of the plasma cortisol levels of normal subjects showed a consistent rise in cortisol during alcohol loading under the conditions of the observations, but in hospital patients admitted with acute alcohol intoxication, variability in the experimental conditions masked any consistent changes. Large variations in method reproducibility as well as subject differences affected results from the measurement of 6βOHF and chloroform extractable 17-hydroxycorticosteroids in one normal and four alcoholic subjects, rendering apparent initial differences insignificant. The results suggest, but do not demonstrate, that alcohol ingestion may divert normal cortisol metabolism into a pathway leading to the production of 6βOHF. Urinary steroid profiles obtained from two normal subjects, one normal subject under conditions of alcohol load and one alcoholic subject suggest that any effects of alcohol on cortisol metabolism are subtle and would require study of a large number of cases to define them. This work has served to delineate the faults and potential of various approaches to the study of cortisol metabolism and the possible effects of alcohol thereon. It would seem that their application in carefully designed and well controlled experiments to a larger number of subjects is necessary to obtain the information desired.
Keywords: Hydrocortisone; Alcohol body; Metabolism